PENGARUH PENGGUNAAN APLIKASI WHATSAPP DAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR SISWA SMP SWASTA KARTIKA 1-4 PEMATANGSIANTAR TAHUN AJARAN 2021/2022 - Jayanti, Fitri Dwi; Piliang, Fenny Mustika; Damanik, Risjunardi (Jurnal Metabio, 2024)
This study aims to examine the Effect of Using WhatsApp and Google Classroom Applications on Student Learning Outcomes. This study is a quantitative study. The study population was 105 students consisting of 3 classes. Sampling was carried out by Cluster Random Sampling, namely class VIII-A using the WhatsApp application and VIII-B using the Google Classroom application, the number of each class was 35 students. The research instrument used a test. Based on the results of hypothesis testing using the t test, as obtained tcount 5.511> ttable (1.994) at a significance level of 0.000 <0.05. Based on this, it can be concluded that the Sig. value <0.05 and the tcount value> ttable, which means that H_0 is rejected and 〖 H〗_a is accepted, thus there is a significant influence between the values in the experimental class and the values in the control class. Based on the results of hypothesis testing using the F test, as obtained the Fcount value is greater than Ftable (15.201> 3.128) and the sig. value. smaller than 0.05 (0.003 <0.05). Thus, Ha is accepted and H0 is rejected, meaning that there is a significant influence if learning is carried out using the WhatsApp and Google Classroom applications on the learning outcomes of class VIII students of SMP Swasta Kartika 1-4 Pematang Siantar in the 2021/2022 academic year.